The disabled living centre: what does it do? - Chamberlain, M. A. (1988)
Seventy five consecutive users of the Leeds disabled living foundation were surveyed. Two thirds of these users were at least moderately severely disabled. Forty eight of the 65 people (74%) who completed the questionnaire were recommended aids, and 33 had received some at the end of the survey. Only 10 of 28 people had received recommended adaptations. Few referrals were made to the centre by doctors. It is important that they tell their patients of this useful service.